2013
DOI: 10.1016/j.scitotenv.2013.03.095
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance, detection and recognition of wind turbine noise

Abstract: Annoyance, recognition and detection of noise from a single wind turbine was studied by means of a two-stage listening experiment with 50 participants with normal hearing abilities. In-situ recordings made at close distance from a 1.8-MW wind turbine operating at 22 rpm were mixed with road traffic noise, and processed to simulate indoor sound pressure levels at L Aeq 40 dBA. In a first part, where people were unaware of the true purpose of the experiment, samples were played during a quiet leisure activity. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 32 publications
(31 reference statements)
2
26
0
Order By: Relevance
“…Most likely, people will focus more on the highway noise and could take it stronger into account while rating. Similar effects were found in other noise-related studies (Van Renterghem, Bockstael, De Weirt, & Botteldooren, 2013).…”
Section: Focused Analysis Of the Audio-visual Environmentsupporting
confidence: 90%
“…Most likely, people will focus more on the highway noise and could take it stronger into account while rating. Similar effects were found in other noise-related studies (Van Renterghem, Bockstael, De Weirt, & Botteldooren, 2013).…”
Section: Focused Analysis Of the Audio-visual Environmentsupporting
confidence: 90%
“…The test sounds used were (1) sound from moving cars, passing at a rate of 1-4 per second; (2) broadband sound with the same spectrum as wind turbines and (3) narrowband sound that could be modulated at 1, 2 and 4 Hz. All three types of sound had modulation depths typical for wind turbines at 3, 6 and 9 dB similar to Van Renterghem et al [84], or zero (no modulation). Results showed that AM did increase annoyance in the case of broadband sound and passing cars, but not for the narrow band sound.…”
Section: Noise Annoyancesupporting
confidence: 75%
“…[89,95,96]. In both studies [93,94] attention was given to expectations on the level of annoyance and the level of awareness ('notice') of the characteristics and prominent sounds of wind turbines [84]. The influence of these factors has been found in many studies regarding the effects of other sound sources [97].…”
Section: Social Aspectsmentioning
confidence: 99%
“…Wind turbine noise (WTN) can be difficult to distinguish from ambient sound (Pedersen and Halmstad, 2003;Van Renterghem et al, 2013) and varies with weather conditions. As a result, calculations can be more representative of long-term levels than estimates based solely on measurements (ISO, 2007).…”
Section: Introductionmentioning
confidence: 99%